Converting bacteriophage for sporulation and crystal formation in Bacillus thuringiensis. - Perlak, F J (1979)
Bacteriophage TP-13, a converting phage for sporulation and crystal formation in Bacillus thuringiensis, was isolated from soil. The phage converted anoligosporogenic (sporulation frequency, 10(-8), acrystalliferous mutant to spore positive, crystal positive at a high frequency. Each plaque formed by TP-13 in a lawn of sensitive cells contained spores and crystals. These spores were heat stable, and each one was capable of producing a plaque from which TP-13 could be reisolated. Conversion of cells to sporulation and crystal formation was independent of the ho-t used for TP-13 propagation. When converted cells were cured of TP-13, they lost the ability to produce spores and crystals. Incubation of TP-13 with antiserum prepared against purified phage particles prevented conversion. TP-13 has some characteristics similar to those of SP-15 and PBS-1, including large size, morphology, and adsorption specificity of motile cells. TP-13 mediated generalized transduction in several strains of B. thuringiensis at frequencies of 10(-6) to 10(-5). Comparison of cotransduction values indicated that TP-13 transduced considerably larger segments of deoxyribonucleic acid than CP-51 or TP-10, two other transducing phages for B. thuringiensis.